(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
As perschedule, the Investigator visited each and every institution. Sections werechosen randomly & then students were selected randomly. The administratingconditions for all the students were kept as constant as possible beforestarting. The students were seated comfortably in their classroom, where therewas no outside disturbance. Investigator explained the purpose of the tests tothe subjects. The subjects were told that this was not an examination rather itis the collection of general information. They wererequired to give their true, free and frank opinion. It was made to them thattheir views would be kept strictly confidential. They were also ensured that their replieswould be used only for the research purpose. The rapport was establishedbetween them. The respondents weregiven test booklets one by one. For each tool, instructions were given.